1996
DOI: 10.1080/00071669608417910
|View full text |Cite
|
Sign up to set email alerts
|

Performance of broiler chicks fed on alkali‐treated neem (Azadirachta indica) kernel cake as a protein supplement

Abstract: 1. An experiment was conducted to evaluate growth and nutrient efficiency of broiler chicks from 3 to 42 d fed on diets containing alkali-treated neem (Azadirachta indica A. juss) kernel cake (NKC) as a protein supplement in place of peanut meal (PNM). 2. NKC was treated with sodium hydroxide at 10 (ANKC 1) or 20 g (ANKC 2)/kg and incorporated into the test diets at 135 or 300 g/kg to replace 50 (low-L) or 100 (High-H)% of the PNM protein of the reference diet. 3. Despite comparable retentions of dry matter an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 4 publications
4
7
4
Order By: Relevance
“…Diets containing turmeric alone recorded lowest value of hemoglobin whereas in combination with neem and vitamin E the values were higher indicating the additive effect. These findings were in agreement with Nagalakshmi et al (1996) who opined that neem possess strong influence on the hematological traits in broilers particularly hemoglobin. Contrary to our findings, Biu et al (2009) and Akbari et al (2008) opined that inclusion of neem and vitamin E at higher levels in the diets of broilers significantly decreases hemoglobin concentrations.…”
Section: Hemoglobinsupporting
confidence: 82%
See 1 more Smart Citation
“…Diets containing turmeric alone recorded lowest value of hemoglobin whereas in combination with neem and vitamin E the values were higher indicating the additive effect. These findings were in agreement with Nagalakshmi et al (1996) who opined that neem possess strong influence on the hematological traits in broilers particularly hemoglobin. Contrary to our findings, Biu et al (2009) and Akbari et al (2008) opined that inclusion of neem and vitamin E at higher levels in the diets of broilers significantly decreases hemoglobin concentrations.…”
Section: Hemoglobinsupporting
confidence: 82%
“…The dietary inclusion of neem alone in the diet of broilers significantly (P≤0.05) increased TLC value as compared to that of other treatments and control. The present findings were in contrary to the findings of Esonu et al (2006) who found significant reduction in circulatory leukocytes on feeding 10 % neem leaf meal layer diet and to Nagalakshmi et al (1996) and Akbari et al (2008) who reported no significant effect of inclusion of neem on total leukocyte count in broiler diet. The result on the effect of turmeric obtained in the present study were in line with the findings of Kumari et al (2007) who reported no negative effect on circulating leukocytes in broilers.…”
Section: Total Leukocyte Countcontrasting
confidence: 57%
“…This study has revealed that tulsi extract had no significant effect on the hematological parameters (Table 4). This findings, however, does not agree with Nagalakshmi et al (1996) and Gowda et al (1998) who reported that bitter principles of medicinal plants possess a strong influence on hematological traits particularly PCV and Hb of subjects, depending on their nutritional status.…”
Section: Resultscontrasting
confidence: 54%
“…This study has revealed that NTL extract had no significant effect on the hematological parameters (Table 4). This finding, however, does not agree with Nagalakshmi et al (1996) and Gowda et al (1998) who reported that bitter principles of medicinal plants possess a strong influence on hematological traits particularly PCV and Hb of subjects, depending on their nutritional status. Supplementation with neem and tulsi extract was more profitable than control group (Table 3) but the difference was not significant (p>0.05).…”
Section: Resultscontrasting
confidence: 54%